Induced sputum or gastric lavage for community-based diagnosis of childhood pulmonary tuberculosis?. Issue 3 (1st October 2008) - Hatherill, M; Hawkridge, T; Zar, H J; Whitelaw, A; Tameris, M; Workman, L; Geiter, L; Hanekom, W A; Hussey, G
Abstract : Objectives: To compare the diagnostic yield of Mycobacterium tuberculosis from induced sputum (IS) and gastric lavage (GL) among children in a community setting. Methods: Specimen-collection methods for bacteriological confirmation of pulmonary tuberculosis (PTB) were compared during a tuberculosis vaccine trial near Cape Town, South Africa (2001–2006). Children with a tuberculosis contact or compatible symptoms were investigated for suspected PTB. Diagnostic yields from 764 paired IS and GL specimens were compared in 191 culture-confirmed cases. Measurements and main results: The crude yield of M tuberculosis was 10.4%, n = 108 by IS (5.8%) and n = 127 by GL (6.8%), from a total of 194 cases, of which three had incomplete IS/GL specimen pairs. Agreement between IS and GL was poor (κ = 0.31). The comparative yield of a single IS sample (38%) was equivalent to a single GL sample (42%), with a difference in yield of −4% (95% CI −15% to +7%). The combined yield of same-day IS and GL specimens (67%) was equivalent to two consecutive GL specimens (66%), with a difference in yield of 1% (95% CI −9% to 11%), but significantly greater than two consecutive IS specimens (55%), with a difference in yield of 12% (95% CI 2% to 21%). The adjusted odds of a M tuberculosis culture were increased by a positive tuberculin skin test or chest radiograph compatible with PTB. Conclusions: In this community setting, the diagnostic yield of a single IS sample was equivalent to that of a single GL sample. The optimal diagnostic yield may be obtained from paired IS and GL specimens taken on a single day or two GL specimens taken on consecutive days.